2008
DOI: 10.1111/j.1467-8578.2008.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

FOCUS ON PRACTICE: Encouraging children to think in more inclusive ways

Abstract: This article explores the possible contributions that children can make in educational settings that aim to move towards greater inclusion. In constructing her debate, Kyriaki Messiou, lecturer in education in the Centre for Educational Studies at the University of Hull, draws on understandings gained through an ethnographic study carried out in a primary school in Cyprus. She used qualitative methods to collect her data, carrying out participant observations and semi-structured interviews with all the childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…Moreover, in such group contexts, the researcher could make use of a range of activities that have been found effective in eliciting the views of children and young people in ways that empower them by giving them greater control over the interview process (see Thomas, ). The exploration of particular techniques for interviews with children in research on inclusion has also been reported to have positive outcomes (Messiou, ) and future research could take advantage of these developments.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Moreover, in such group contexts, the researcher could make use of a range of activities that have been found effective in eliciting the views of children and young people in ways that empower them by giving them greater control over the interview process (see Thomas, ). The exploration of particular techniques for interviews with children in research on inclusion has also been reported to have positive outcomes (Messiou, ) and future research could take advantage of these developments.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Finalmente, aunque se ha logrado avanzar hacia la inclusión educativa en materia de derechos y poco han sido las reformas en materia de formación profesional, queda recorrer un largo camino para lograr una transformación profunda del sistema educativo de orientación a atención a la diversidad, los esfuerzos realizados no son suficientes, lo que hace necesario seguir continuar movilizando a las Instituciones de Educación Superior para que desarrollen procesos educativos de participación, y sistemas inclusivos de calidad que garanticen la formación de competencias profesionales y laborales de orientación inclusiva, y que permitan el aprendizaje de todos los estudiantes sin discriminación (Messiou, 2016;Elizalde et al, 2016, p.101).…”
Section: )unclassified
“…Child interviews focused on positive and negative experiences at home and at school. A participatory tool called the 'Feeling Dice' (Messiou, 2008) was used to help prompt discussion and increase comfort levels with younger children and older children with intellectual impairments. The different sides of the dice depict simple faces with different emotions (happy, sad, joyful, angry), which the children can draw themselves, and when the dice is thrown it prompts a discussion.…”
Section: Ethical Considerationsmentioning
confidence: 99%